Choice and control in social care: Experiences of older self‐funders in England. (5th August 2019) - Baxter, Kate; Heavey, Emily; Birks, Yvonne
Abstract: This paper considers the experiences of older self‐funders in England in the context of policies promoting choice and control. Self‐funders are people who are not state‐funded; they pay for social care from their own resources. Choice and control have been operationalized through personal budgets, based on the assumption that managing resources enhances ability to access appropriate care and support. This paper uses data from 40 qualitative interviews with self‐funders and their relatives, and 19 with professionals. It explores the impact of the financial and social capital that self‐funders are assumed to have and asks how older self‐funders experience choice and control. The study found that older self‐funders drew on personal experiences, family, and friends for information; were reluctant to spend their wealth on care due to competing priorities; and felt they had more control over the timing of decisions than people who were state‐funded. Personal wealth appears to be perceived differently to funds "gifted" to people through cash for care schemes.